Identification of Farmers' Local Wisdom in Managing Lebak Swamp Land during the Covid-19 Pandemic Period in Keramasan Village, Palembang City, Indonesia - Muhammad Arbi; Yulian Junaidi; Indri Januarti; Serly Novita Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Utilizing the potential that exists in oneself and the surrounding environment is one way to be able to adapt to current conditions. The COVID-19 pandemic has also had an impact on the condition of farming activities in Keramasan Village. In addition to the distribution of production results, the pandemic also has an impact on the production process, resulting in a decrease in production at the lowland swamp farmer level. But on the other hand, farmers in Keramasan Village have their own local wisdom in carrying out farming activities. This attracted the attention of researchers to examine how existing local wisdom supports rice farming activities during the pandemic and how it affects the household income of rice farmers in wetlands (sub optimal).The results of this study indicate that the majority of the community still maintains local wisdom of rice management in the Lebak wetlands, especially in cultivation. Local wisdom of farmers in managing rice crops includes seed procurement, planting, harvesting, and operations post-harvestLocal wisdom in procuring seeds is that farmers still use the seeds from the previous harvest, borrow and use the planting and seedling system. Local wisdom about harvesting uses simple tools such as sickles and machetes. Finally, it is post-harvest local wisdom for farmers to sell their harvests directly to middlemen who come to their land during the harvest process.